Current Advances in Neuroprotective Effects and Relative Mechanisms of Sesamin - Deqi JIANG; Juanfeng MO; Shuilian BIN; Yinting TUO; Ziqiang LI; Xinyi LI; Ruilan LIANG (Shipin gongye ke-ji, 2022)
Sesamin is an important lignan compound, which is mainly isolated from sesame seeds. Sesamin has a variety of biological activities such as anti-oxidative stress, anti-inflammatory, anti-apoptosis, reducing β-amyloid aggregation, anti-excitatory toxicity, promoting dopamine production and neurotrophic factor expression. Sesamin can effectively prevent and treat Alzheimer's disease, Parkinson's disease, traumatic brain injury, depression and anxiety, cerebral ischemia injury and other neuropsychiatric diseases at the animal and cellular levels. In this paper, the neuroprotective effects and related mechanisms of sesamin in vivo and in vitro experiments are reviewed in order to provide scientific basis for the development and application of sesamin-related health care products and food additives.